Caring for the carers: a COVID-19 psychological support programme. Issue 2 (18th June 2021) - Lamb, Di; Simms, A; Greenberg, N; Withnall, R D J
Abstract : The outbreak of COVID-19 and the subsequent pandemic brought unprecedented worldwide challenges born out of a rapidly escalating health and economic crisis. From emergency planners to healthcare workers on the front line, and everyone in between, the pandemic, and the uncertainty surrounding it, was likely to become a significant stressor, one with no immediate solution but with the potential to cause enduring distress beyond its conclusion. The UK Defence Medical Services recognised the need to provide an evidence-based programme of care intended to support personnel transitioning from assisting the national response back to normal duties. This was informed by a narrative review that targeted literature exploring strategies for supporting the mental health and well-being of healthcare workers during 21st-century infectious disease outbreaks. The literature identified the experiences most likely to cause enduring distress, which comprised morally challenging decisions, vulnerability, death and suffering, professional and personal challenges, and expectations. The opportunity to find meaning in these experiences, by discussing them with peers who share a contextual understanding, is important to limit the longer-term psychosocial impact of such events. This paper will discuss the design considerations and planned implementation strategy of the Recovery, Readjustment and Reintegration Programme to limit the incidence of distress or longer-term mental ill health among military personnel.